Acetyl-glucomannan from Dendrobium officinale: Structural modification and immunomodulatory activities - Guo, Xiaoyu; Yang, Mingguan; Wang, Changlu; Nie, Shaoping; Cui, Steve W.; Guo, Qingbin (Frontiers in Nutrition, 2022)
To understand the mechanisms of immunomodulatory effect, Dendrobium Officinale Polysaccharides (DOP) were treated by ultrasound and mild base separately to generate fractions of various weight-average molecular weight (Mw) and degrees of acetylation (DA). The structural features, conformational properties, functional properties and immunomodulatory activities of original and modified DOPs were investigated. Ultrasonic treatment decreased the Mw and apparent viscosity and improved the water solubility of DOP. Mild base treatment remarkably reduced the DA and the water solubility, while the overall apparent viscosity was increased. Conformational analysis by triple-detector HPSEC showed that the molecular chain of DOP turned more compact coil conformation with decreased DA. Results from the macrophages RAW 264.7 analysis showed that samples sonicated for 200 min (Mw 34.2 kDa) showed the highest immune-regulation effects. However, the immunomodulatory effects of the samples after de-acetylation were all compromised compared to the original DOP. This study inspires further research to establish the structural-immunomodulatory relationships, which promote the application of DOP in both the food and medicine fields.